Channel and delay estimation for base-station-based cooperative communications in frequency flat-fading channels - Hongjun Xu (South African Journal of Science, 2010)
Base-station - based cooperative communication is an asynchronous cooperative communication system. The challenge therein is to estimate the relative delay between the transmitters in the system. A channel and delay estimation algorithm based on the distributed Alamouti scheme has been previously discussed for the asynchronous cooperative system. The algorithm only makes accommodation for positive delay, that is, when data from Transmitter one always arrives at the receiver before data from Transmitter two. In reality, the data from Transmitter one does not always arrive at the receiver before data from Transmitter two in the asynchronous cooperative system, because of the constantly changing mobile environment in the system. This paper extends the algorithm to accommodate both positive and negative delays, which is when the data from Transmitter one arrives at the receiver before or after data from Transmitter two, in a Rayleigh block fat-fading channel. Simulation results show that the Cram ér - Rao lower bound for channel and delay estimation is achieved for different delay values. The symbol error rate performance is also achievable compared to the channel and the delay is known at the receiver.